2004
DOI: 10.1002/ajh.20167
|View full text |Cite
|
Sign up to set email alerts
|

Role of ELISA D‐dimer test in patients with unstable angina pectoris presenting at the emergency department with a normal electrocardiogram

Abstract: Patients with unstable angina pectoris and acute myocardial infarction have higher than normal D-dimer levels. The aim of the study was to determine the value of the D-dimer test in patients with unstable angina pectoris and a normal electrocardiogram on presentation at the emergency department. The study sample included 81 patients who met these criteria. Blood samples collected at admission were subjected to ELISA D-dimer. Findings were correlated with coronary risk factors, use of cardiac medications, blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
1
13
1
Order By: Relevance
“…We demonstrated that combined use of a lower threshold value of D-dimer test (200 ng/ml) and cTnI test could raise the sensitivity to 98.4% and help triage an additional 20% of low risk patients with typical chest pain and non-diagnostic cTnI and ECG tests. In contrast to previous findings, we did not find D-dimer a highly specific test capable of differentiating patients with MI from other patients with nonspecific chest pain in the early stage [14][15][16][17][18]. Our results echo the conclusion of some recent works, which also did not find added clinically meaningful information to the traditional cardiac necrosis markers [20][21][22].…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…We demonstrated that combined use of a lower threshold value of D-dimer test (200 ng/ml) and cTnI test could raise the sensitivity to 98.4% and help triage an additional 20% of low risk patients with typical chest pain and non-diagnostic cTnI and ECG tests. In contrast to previous findings, we did not find D-dimer a highly specific test capable of differentiating patients with MI from other patients with nonspecific chest pain in the early stage [14][15][16][17][18]. Our results echo the conclusion of some recent works, which also did not find added clinically meaningful information to the traditional cardiac necrosis markers [20][21][22].…”
Section: Discussioncontrasting
confidence: 76%
“…Previous studies have demonstrated that the elevation of several molecular markers of thrombin generation are associated with MI and proved to increase the diagnostic sensitivity for MI [14][15][16][17][18]. However, little is known of their potential role in the triage and risk stratification of patients with chest pain in the ED.…”
Section: Introductionmentioning
confidence: 99%
“…As the specific degradation product of fibrin, Ddimer is the major marker of thrombosis and thrombolysis. [13][14][15][16] Elevated concentration of D-dimer in peripheral blood indicates hyper-coagulation or formation of fresh thrombosis and increased fibrinolysis. 17) These symptoms are also likely related to the formation and coagulation of fibrin in blood vessels and unstable atherosclerotic plaque activities.…”
Section: Discussionmentioning
confidence: 99%
“…Further, patients in whom the first presentation of coronary heart disease is with AMI may have higher D-dimer levels than patients who first present with stable angina (186). A weak but statistically significant correlation has been demonstrated between plasma D-dimer levels and severity of coronary disease on angiography in patients with unstable angina (187,188). In a cohort of 54 patients who were diagnosed with unstable angina and underwent coronary angiography, D-dimer levels (cutoff 270ng/ml) predicted significant coronary disease on angiography with sensitivity 70%, specificity 50%, PPV 86%, NPV 72%.…”
Section: D-dimermentioning
confidence: 99%